OP0104 Apremilast, an Oral Phosphodiesterase 4 Inhibitor, in Patients with Psoriatic Arthritis Including Current Skin Involvement: Results of a Phase 3, Randomized, Controlled Trial. (23rd January 2014) - Birbara, C.; Blanco, F. J.; Crowley, J. J.; Hu, C.; Stevens, R.; Edwards, C. J.
Abstract : Background: Apremilast (APR), an oral phosphodiesterase 4 inhibitor, works intracellularly to modulate inflammatory mediators. Objectives: PALACE 3 compared APR vs placebo (PBO) in patients with active psoriatic arthritis (PsA) and at least 1 ≥2-cm psoriatic lesion at baseline (BL) despite prior DMARDs and/or biologics. Methods: Patients were randomized 1:1:1 to PBO, APR 20 mg BID (APR20), or APR 30 mg BID (APR30) stratified by BL DMARD use. At wk 16, patients with <20% reduction in swollen and tender joint counts (SJC, TJC) were required to be re-randomized to APR20 or APR30 (early escape) if first randomized to PBO or remained on the initial APR dose. Patients continued treatment through wk 24. Stable concurrent DMARD therapy was allowed (MTX, sulfasalazine, leflunomide, or combination). Efficacy analyses were conducted using the per-protocol population (N=486). Missing data were handled using NRI for ACR response at wk 16 and LOCF for secondary endpoints. Results: 505 patients were randomized and had comparable BL characteristics (mean TJC 20.0, SJC 11.4, HAQ-DI 1.157, DAS-28 4.57); 27.9% had prior biologic exposure and 8.7% were considered biologic failures. At BL, 60.6% were taking DMARDs, of which 85.6% were taking MTX (mean dose, 14.75 mg/wk). At wk 16, significantly more patients receiving APR20 (29.4%; P =.02) and APR30 (42.8%; P <.0001) achieved the primary endpoint of ACR20 vs PBO (18.9%). Comparable results were seen with APR monotherapy or as combination therapy with DMARDs. At wk 24, significant improvements in secondary endpoints were seen with APR vs PBO (Table). APR was well tolerated. Adverse events (AEs) occurring in ≥5% of any group were diarrhea, nausea, headache, and URTI. Of APR-treated patients with AEs, the majority (>92%) AEs were mild or moderate. Discontinuations due to AEs were low across all treatment arms (6-8%). Serious AEs occurred in 9 (PBO), 3 (APR20), and 6 (APR30) patients. No systemic opportunistic infections (including reactivation or de novo TB) or lymphoma was observed. There was no greater risk of cardiovascular events. Conclusions: APR significantly improved signs and symptoms of PsA and associated psoriasis and resulted in statistically and clinically meaningful improvements in physical function. APR was generally well tolerated with no new safety or laboratory signals detected. Disclosure of Interest: C. Birbara Grant/research support from: Amgen, Lilly, Pfizer, Incyte, Merck, Bristol-Myers Squibb, F. Blanco Consultant for: Pfizer, Bioiberica, Gebro Farma, J. Crowley Grant/research support from: Abbvie, Amgen, Celgene, Janssen, Merck, Pfizer, Speakers bureau: Abbvie, C. Hu Employee of: Celgene Corporation, R. Stevens Employee of: Celgene Corporation, C. Edwards Grant/research support from: Pfizer, Consultant for: Samsung, Roche, Celgene, Speakers bureau: Roche, Pfizer, Abbott, GSK